Anesthetic management of acute right heart failure in patients with pulmonary embolism undergoing AngioJet pulmonary embolectomy: a case report - Zhang, Shasha; Meng, Fangeng; Zhou, Chao; Zhang, Yiwen; Liu, Huaqin; Rong, Yuanyuan (Frontiers in Oncology, 2024)
BackgroundEarly mortality rate in patients with high-risk pulmonary embolism(PE) is extremely high. Prompt and effective reduction of the thrombus load, and restoration of pulmonary circulation may successfully treat such patients. For patients with hemodynamic instability and high-risk acute PE, the guidelines recommend catheter directed therapy (CDT). Such patients are at increased risk during perioperative period and need considerable attention from anesthesiologists. Herein, we describe a case of acute right heart failure in a patient undergoing AngioJet PE.Case summaryA 59-year-old woman with lung cancer had been prescribed anticoagulant therapy for PE six months ago. She discontinued using the drugs on her own two months ago. One week ago, she developed chest tightness and shortness of breath, leading to the diagnosis of another PE episode. An AngioJet pulmonary embolectomy and inferior vena cava filter implantation were urgently needed under general anesthesia. During surgery, after inserting the AngioJet Solent catheter into the right lower lobe artery, she developed severe hypotension 5 s after thrombolysis with urokinase, with no obvious improvement after administration of pressor drugs; hence, pulmonary vasospasm was considered. The anesthesiologist implemented a series of resuscitation measures such as discontinuing the surgical stimulation; chest compressions; and administering pure oxygen, vasoactive drugs, and adequate anticoagulation to ensure patient safety during the perioperative period and a smooth operation.ConclusionPulmonary artery spasm caused by AngioJet pulmonary artery embolization is a rare complication and may be life-threatening. Low left ventricular output and acute right heart failure may occur due to pulmonary spasm, which requires early identification, inhalation of pure oxygen, circulatory support, anticoagulation, and thrombolysis.